Anacardato de cálcio em associação com ácido cítrico na ração de frangos de corte - Santos, Edibergue Oliveira dos (2023)
The aim of this study was to evaluate the association of calcium anacardate and citric acid on hematological and biochemical parameters of the blood, digestive system, performance, carcass characteristics, lipid oxidation of blood serum and liver, fresh meat quality parameters, concentration of compounds phenolics of fresh meat, potential and antioxidant activity of fresh meat, lipid oxidation of fresh and stored meat, bone parameters and the incidence of black bone syndrome. For this, 768 male Ross broiler chicks, 1 day old, were distributed in a completely randomized experimental design with eight treatments and six replications of 16 birds. The treatments consisted of rations, which were: negative control ration (without growth promoter and without anticoccidial); positive control ration (with growth promoter and with anticoccidial); feed with 0.25% AnCa (Calcium anacardate) + 0.25% AC (Citric acid); feed with 0.50% AnCa + 0.25% CA; feed with 0.50% AnCa + 0.50% CA; feed with 0.75% AnCa + 0.25% CA; feed with 0.75% AnCa + 0.50% CA; feed with 0.75% AnCa + 0.75% AC. According to the results, in relation to the birds fed with negative control ration, the different combinations of anacardate and citric acid reduced the level of uric acid in the blood of the birds at 21 days of age. The relative weight of the duodenum was greater with the addition of 0 .75% AnCa + 0.50% AC and 0.75% AnCa + 0.75% AC at 21 and 42 days of age. The blood antioxidant capacity increased with the addition of diets containing 0.50% AnCa + 0, 25% AC; 0.50% AnCa + 0.50% AC; 0.75% AnCa + 0.25% AC; 0.75% AnCa + 0.50% AC and 0.75% AnCa + 0.75% AC at 42 days of age. The blood lipid oxidation decreased with all doses of AnCa + AC at 42 days of age and the Liver lipid oxidation decreased with all doses of AnCa + AC at 21 and 42 days of age. As for performance, in the period from 1 to 42 days of age, feed conversion improved with combinations of 0.50% AnCa + 0.50% CA; 0.75% AnCa + 0.25% AC; and 0.75% AnCa + 0.50% AC. The meat antioxidant potential (DPPH) and activity (ABTS) increased with the addition of 0.50% AnCa + 0.50% AC in relation to the negative control and positive control treatments. As for meat phenolic compounds, all treatments with combinations of AnCa + CA showed higher concentrations compared to the negative control treatment. In the evaluation of the lipid stability of the meat, it was observed that the fresh and stored meat from birds fed with the different combinations of AnCa + AC presented better values compared to the negative control treatment. There was no significant difference between treatments for bone parameters and the incidence of black bone syndrome. It is concluded that the concentration of blood uric acid in chickens up to 21 days old reduces with the addition of calcium anacardate and citric acid at all levels tested. Thus, feed intake and weight gain decrease with the addition of combinations of 0.50 % AnCa and 0.25% AC; 0.50% AnCa and 0.50% AC; 0.75% AnCa and 0.25% AC; 0.75% AnCa and 0.50% AC and 0.75% AnCa and 0.75% AC. However, when considering the total rearing period, the addition of 0.50% AnCa + 0.50% AC can be recommended due to this combination improves the oxidative state in the blood and liver of chickens at 42 days of age and food conversion. The combination of 0.50% AnCa + 0.50% CA was also sufficient to obtain the benefits of improving the concentration of phenolic compounds, activity and antioxidant capacity of fresh meat and reduction in lipid oxidation of fresh and meat stored for 60 days. Growth and bone quality and the incidence of black bone syndrome are not altered with the addition of up to 0.75% calcium anacardate in association with 0.75% citric acid.